Robotic median arcuate ligament release: a video vignette - Marie-Thérèse Maréchal; Nikolaos Koliakos; Dimitrios Papaconstantinou; Luca Pau; Nicolas Boyer; Mathilde Poras; Georgios Katsanos; Eleonora Farinella (Journal of Minimally Invasive Surgery)
Median arcuate ligament syndrome (MALS) poses a rare challenge in diagnosis and management. We present a case of MALS in a 50-year-old male with recurrent epigastric pain, vomiting, and diarrhea. Diagnostic imaging revealed celiac artery stenosis and gastroduodenal artery collateral dilatation. Robotic-assisted median arcuate ligament release successfully alleviated symptoms. Utilizing the da Vinci X system (Intuitive Surgical, Inc.), the procedure involved meticulous dissection of the celiac artery and surrounding tissue. Postoperative duplex ultrasound confirmed improved arterial flow. Literature underscores the diagnostic hurdles of MALS and the advantages of minimally invasive approaches over conventional open surgery. The robotic approach may help smoothen the learning curve associated with this procedure, by providing improved operative flexibility. Patient outcomes are excellent, with long-term symptom relief in most cases.